2020
DOI: 10.1055/a-1337-5504
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Catalyzed C–F/N–H Annulation of 2-(2-Fluoroaryl) N-Heteroaromatic Compounds with Alkynes: Activation of C–F Bonds

Abstract: The reaction of 2-(2-fluoroaryl) N-heteroaromatic compounds, such as benzimidazole and indole derivatives, with internal alkynes in the presence of a catalytic amount of a nickel complex results in C–F/N–H annulation with alkynes. The reaction shows a high functional group compatibility. The presence of a strong base, such as KOBu­ t or LiOBu t , is required for the reaction to proceed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 7 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…4,5,24 Several studies from different areas in the world reported that male gender is an independent risk factor for PIU. 22,23,25,26,27 Moreover, Anderson et al 17 reported that the majority of the findings across different cultural samples support that males being at higher risk, and the difference between males and females regarding PIU is widening over time . Different hypotheses and interacting factors were proposed to explain the differences revealed that males being targeted by the marketing strategies of higher PIU risk applications such as online games 26,28 and also males in general are being at higher risk of developing addiction-related behaviors as PIU.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,24 Several studies from different areas in the world reported that male gender is an independent risk factor for PIU. 22,23,25,26,27 Moreover, Anderson et al 17 reported that the majority of the findings across different cultural samples support that males being at higher risk, and the difference between males and females regarding PIU is widening over time . Different hypotheses and interacting factors were proposed to explain the differences revealed that males being targeted by the marketing strategies of higher PIU risk applications such as online games 26,28 and also males in general are being at higher risk of developing addiction-related behaviors as PIU.…”
Section: Discussionmentioning
confidence: 99%
“…Gram-scale synthesis was also well conducted and one of the synthesized derivative was further converted into other useful products. The authors also performed photophysical studies with the synthesized indolo [ A similar reaction was performed by Chatani and coworkers [71] Utilizing ortho-functionalized diaryl acetylenes 110 and boronic acids 111 as the precursors for synthesizing diaryl isoquinolines 112 in good yields (up to 83%) via an electrophile driven arylative cyclization reaction was reported by Reddy and coworkers (Scheme 41). [72] Their methodology utilized the catalytic amount of Ni(acac) 2 (10 mol %) as a catalyst, PPh 3 ligand (10 mol %), and Cs 2 CO 3 base (20 mol %).…”
Section: Nickel Catalysismentioning
confidence: 99%
“…A similar reaction was performed by Chatani and coworkers [71] with certain modifications in optimized conditions (Scheme 40). They utilized 2‐(2‐fluoroaryl) N‐heteroaromatics 107 and internal alkynes 108 as the starting materials and utilize Ni(COD) 2 catalyst, Me 4 Phen ligand, and t ‐BuOK base to synthesize various annulated products 109 in good yields.…”
Section: Metal‐catalyzed Synthesis Of Isoquinolinesmentioning
confidence: 99%
“…To evaluate the feasibility of the newly developed amidate-promoted strategy, we extended this strategy to other systems. This strategy was not limited to aromatic amides, but N-heteroaromatic systems, including benzimidazole derivatives, and N-pyrimidinyl aniline derivatives also participated in this C–F/N–H annulation with alkynes to give π-extended heteroaromatic compounds and indole derivatives, respectively (Scheme A) . Carboxylic acids also participated in the reaction to give 1 H -isochromen-1-one derivatives, although the reaction required a high temperature with microwave irradiation (Scheme B) .…”
Section: Ni-catalyzed C–f Bond Functionalization Reactionsmentioning
confidence: 99%